The Leader is a Watchman: A Pragma-Dialectical Reading of Olusegun Obasanjo’s My Watch - Ayo Osisanwo; Sunday Adegbenro (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Olusegun Obasanjo’s My Watch explicates a representation of Nigerian socio-political history and is laden with political arguments. This paper investigates the pragma-rhetorical devices and the strategic patterns utilized by Olusegun Obasanjo in My Watch - a three-volume text.  However, only Volume Two: Political and Public Affairs (PPA) was considered for the analysis. Adopting van Eemeren and Grootendorst’s pragma-dialectical theory of argumentation, this paper analyses Obasanjo’s argument on Odi Military Action and the Third-Term issues as presented in PPA. It identifies five presentational devices: positive pragmatic argument, practs, presuppositions, negative lexicalization, passive construction; and six strategic maneuvering techniques: blame game, smokescreen techniques, prerogative argument, fallacious appeal to authority, ad-hominiem attacks, and ethotic appeal. The paper posits that Obasanjo’s presentational devices and strategic maneuvering techniques are adapted strategically to the beliefs and preferences of his audience.  It concludes that Obasanjo’s narration focuses not on ‘redemption’ but ‘justification’ and the argument adopted the standard strategic maneuvering of political rhetoric which is often polarizing and destructive; therefore, his strategic maneuvering derails.